Comparação dos dados antropométricos de pacientes em dois momentos de uma UTI pediátrica - Costa , Caroline Abud Drumond (2015)
Introduction : The anthropometric nutritional assessment is a necessary way in children undergoing hospital. Despite of the malnutrition is significantly present in a hospital, it calls attention the nutritional transition that the country is going through, where the increase of overweight and obesity is increasing.Studies already show a fall of malnutrition even among patients in the Pediatric Intensive Care Unit. The objective of this study is to compare anthropometric data of patients in two moments of a Pediatric Intensive Care Unit.Methods : A retrospective cohort study, with patients in the Pediatric Intensive Care Unit of a university hospital in two periods of one year long, with four years interval. The data are from the unit's database. The nutritional assessment was performed based on the weight and height measured at the hospitalization moment. Parameters and classification of nutritional status were used recommended by the World Health Organization for the respective age groups. The Body Mass Index for Age was the chosen parameter to assess malnutrition and relate to severity and outcomes. Chi-square and Mann-Whitney test for comparison of patient data between the two moments were used. The differences were considered significant when p <0.05.Results : The total sample of patients was 881 (406, current sample and 475, previous sample). There was a significant reduction by malnutrition in the current sample of patients (p = 0,03).In relation to outcomes, malnourished patients of the previous sample had a significant association with mortality and prolonged length of stay, while malnourished of the current study, did not show this association. Malnourished of the previous sample also showed significant association with severity on admission (Mensured by Pediatric Index Mortality 2), which was not observed in the current sample of malnourished ones.Conclusion : There was a significant reduction of malnutrition among patients of the same PICU when we compare two moments, suggesting that the nutritional transition is also present among pediatric critical patients. The current sample of malnourished also had better outcomes compared to the previous one. More studies are needed in order to confirm this nutritional transition and its impact among this group of patients.